Proving Corruption in the Investigative and Judicial Practice of Ukraine: Problems and Solutions - R. L. Stepaniuk; V. V. Kikinchuk; M. H. Shcherbakovskyi (Law and Safety)
The work is based on the analysis of the scientific literature, criminal and criminal procedural legislation of Ukraine, which regulates public relations associated with the identification, detection, investigation and judicial review of cases of illegal benefit by officials, on the precedents of the European Court of Human Rights on this issue, as well as the study and summarizing the materials of 200 criminal cases on illegal benefits considered by the courts of Ukraine in 2015-2019. It has been established that proof of corruption offences in criminal proceedings is the activity of the subjects of criminal proceedings, which consists of collecting, assessing and verifying factual data in order to establish circumstances relevant to the investigation. At the same time, procedural and tactical mistakes, as well as abuses on the part of prosecution agents, which lead to deficiencies in the process of proving the guilt of officials who commit corruption offences, are very common in the practice of the Ukrainian law enforcement agencies in this area.